Depoimento sem dano: implicações nas atribuições do assistente social - um estudo no Tribunal de Justiça do Estado de São Paulo - Luiz, Maíla Rezende Vilela (2017)
This dissertation aims to analyze the impact of the Depoimento Sem Dano’s methodology on the social worker's professional work at the Court of Justice of the State of São Paulo - TJ-SP. The research proposal is to discuss how Social Service is involved in the project of children's inquiry, which is being implemented in the TJ-SP, in several Brazilian Courts of Justice, as well as evaluate whether the inquiry of children is the duty of the social assistant worker who works in the Judiciary. Thus, is inquiring children who are victims of sexual violence a social worker's or the magistrate's responsibility? To execute this study, we have used a bibliographical and documentary survey on this subject and selected professionals, among them: lawyers, social workers and models of the representative entity of the professional category. The selected professionals participated in a research that was conducted through interviews and questionnaires. Through the analysis of the data, it was possible to verify some controversies regarding the positioning of the Federal Councils of Social Work and Psychology, the Association of Social Assistants and Psychologists of the TJ-SP and the Association of Social Workers and Psychologists of Brazil, as well as social workers divergent opinions regarding the method mentioned, besides the distortion of the concept of Full Protection by the Brazilian Statute of the Child and Adolescent- ECA